Networked Chaotic Map Model and Its Applications in Color Multiple Image Encryption - Yu-jie Sun; Hao Zhang; Chun-peng Wang; Zhen-yu Li; Xing-yuan Wang (IEEE Photonics Journal, 2020)
In this study, a networked spatiotemporal chaotic map model is proposed based on the traditional coupled map lattice system. In addition, the time delay and variable topology parameters are considered to make the system more practical. The chaotic properties are analyzed using a bifurcation diagram, Lyapunov exponents, and entropies. In addition, institute of standards and technology tests are conducted to further analyze the randomness of the system signal. Based on the proposed system, a three-dimensional encryption algorithm is designed to encrypt multiple color images with scrambling and diffusion at the bit level. Several analyses, including histogram analysis, information entropy analysis, correlation analysis, key sensitivity, differential attack analysis, and resistance analyses, are performed to test the effectiveness and robustness of the proposed multiple image encryption algorithm with a networked chaotic map model.